Small Molecule Inhibitors of Plasminogen Activator Inhibitor-1 Elicit Anti-Tumorigenic and Anti-Angiogenic Activity. - Veronica R Placencio; Atsuhiko Ichimura; Toshio Miyata; Yves A DeClerck (PLoS ONE, 2015)
Numerous studies have shown a paradoxical positive correlation between elevated levels of plasminogen activator inhibitior-1 (PAI-1) in tumors and blood of cancer patients with poor clinical outcome, suggesting that PAI-1 could be a therapeutic target. Here we tested two orally bioavailable small molecule inhibitors of PAI-1 (TM5275 and TM5441) for their efficacy in pre-clinical models of cancer. We demonstrated that these inhibitors decreased cell viability in several human cancer cell lines with an IC50 in the 9.7 to 60.3 μM range and induced intrinsic apoptosis at concentrations of 50 μM. In vivo, oral administration of TM5441 (20 mg/kg daily) to HT1080 and HCT116 xenotransplanted mice increased tumor cell apoptosis and had a significant disruptive effect on the tumor vasculature that was associated with a decrease in tumor growth and an increase in survival that, however, were not statistically significant. Pharmacokinetics studies indicated an average peak plasma concentration of 11.4 μM one hour after oral administration and undetectable levels 23 hours after administration. The effect on tumor vasculature in vivo was further examined in endothelial cells (EC) in vitro and this analysis indicated that both TM5275 and TM5441 inhibited EC branching in a 3D Matrigel assay at concentrations where they had little effect on EC apoptosis. These studies bring novel insight on the activity of PAI-1 inhibitors and provide important information for the future design of inhibitors targeting PAI-1 as therapeutic agents in cancer.